FAKTOR-FAKTOR YANG MEMPENGARUHI KENAKALAN REMAJA DI DESA KUNTU KECAMATAN KAMPAR KIRI - Nurbayti Hasan; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The background of this research is because the more often the delinquency done adolescent not only in the city, even in the village. The purpose of this research is to know the form of juvenile delinquency and factor that be driving her. This study was conducted in Desa Kuntu Kecamatan Kampar Kiri. This study was designed with a quantitative method thedescriptive with the program SPSS 23. The population used was all over the teen residence permit in Desa Kuntu with the age range 10-20 year. The sample in this research amounted 87 people who are students with using the formula Slovin. The results of the study found forms juvenile delinquency in Desa Kuntu is the problem of disturbing peace around with the scores 1490, fight between the groups with the scores 1081, the kind of racing wild with the scores 440, and most dominant is the problem of violations of the school with higher scores 1370. The factors that affect juvenile delinquency in Desa Kuntu is the influence of the school with the scores 411, the personality of with the scores 1408, family environment with the scores 1116, and most dominant was given the influence of the people with higher scores 1139. After doing all the test, then it can be the concluded of the results are the influence of a significant between the factors that affect with juvenile delinquency in Desa Kuntu Kecamatan Kampar Kiri with the test t :  >  ( 3,200 > 1,662 ) / significant < 0,1  ( 0,002 < 0,1 ). The key word : Adolescent, Juvenile Delinquency, Factors Influence